The Effect of Liquidity, Solvability, and Profitability on Stock Prices in the Mining Subsector - Ramadhan, Muhamad Revi; Matyani, Matyani; Sofyaun, Ashari (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study is to determine the effect of the variables Current Ratio, Debt to Equity ratio and Return On Assets both simultaneously and partially on Stock Prices. The data used are existing sources, both internal and external data and data can be accessed via the internet and information publications. The data used are the financial reports of mining subsector companies listed on the Indonesia Stock Exchange for the period 2021-2024. This study uses a quantitative approach and for analysis tools using SPSS version 25. The data analysis method uses multiple linear regression analysis, classical assumption test, anova test and t test. The results of the analysis show that the Current Ratio variable has a positive and insignificant effect on stock prices, Debt to Equity Ratio has a negative and insignificant effect on stock prices, and Return On Assets has a positive and significant effect on stock prices.